2017
DOI: 10.1017/jfm.2017.193
|View full text |Cite
|
Sign up to set email alerts
|

Destabilisation and modification of Tollmien–Schlichting disturbances by a three-dimensional surface indentation

Abstract: We consider the influence of a smooth three-dimensional (3-D) indentation on the instability of an incompressible boundary layer by linear and nonlinear analyses. The numerical work was complemented by an experimental study to investigate indentations of approximately 11δ 99 and 22δ 99 width at depths of 45 %, 52 % and 60 % of δ 99 , where δ 99 indicates 99% boundary layer thickness. For these indentations a separation bubble confined within the indentation arises. Upstream of the indentation, spanwise-uniform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 30 publications
5
35
0
Order By: Relevance
“…Furthermore, concomitant scenarios of bypass and classical transition have been observed on longer timescales, and their possibly simultaneous occurrence blurs the long-time output of the edge tracking algorithm. To our knowledge, whereas instances of such a coexistence have been reported in more complicated geometries (Xu et al 2017;Canton et al 2019) this coexistence is reported for the first time that in a simulation of an unforced boundary layer flow. A moving box technique allows for a more efficient usage of the computational domain.…”
Section: Discussionsupporting
confidence: 48%
“…Furthermore, concomitant scenarios of bypass and classical transition have been observed on longer timescales, and their possibly simultaneous occurrence blurs the long-time output of the edge tracking algorithm. To our knowledge, whereas instances of such a coexistence have been reported in more complicated geometries (Xu et al 2017;Canton et al 2019) this coexistence is reported for the first time that in a simulation of an unforced boundary layer flow. A moving box technique allows for a more efficient usage of the computational domain.…”
Section: Discussionsupporting
confidence: 48%
“…Finite element methods [24][25][26][27] and the finite volume method [28,29] are very effective tools to solve some partial differential equations (PDEs) on complex geometries, which is applied in a wide range of engineering and biomedical disciplines [30][31][32][33][34]. In this paper, the finite volume method is implemented to calculate the NS equation.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a global mapping technique has been developed which allows the simulation of fluid flows with geometrically periodic variation along homogeneous directions [8,11]. A typical example is to simulate turbulent flows induced by a localised surface deformation in the boundary layer [11]. The computational domain is illustrated in Fig.…”
Section: Turbulent Flowsmentioning
confidence: 99%
“…Recently, the instability methods using the spectral/hp element method have been employed for investigating the stability analysis of vortical flows and controlling wakes of flows past bluff bodies [82,83,84]. With the linearised Navier-Stokes equations, the interaction between instability waves and surface distortion in a 2-D and 3-D boundary layer have been precisely investigated [75,10,11].…”
Section: Hydrodynamic Stabilitymentioning
confidence: 99%
See 1 more Smart Citation